2010
DOI: 10.1007/s11434-010-3201-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of individual amyloid fibrils using atomic force microscopy

Abstract: Compression elasticity of glucagon amyloid fibrils in the transverse direction was investigated by a nanoindentation approach based on atomic force microscopy (AFM). With force-volume mapping, we obtained the correlations between radially applied force and compression of amyloid fibrils, from which the radial compressive elasticity can be deduced. The estimated elastic modulus at three typical locations of fibrils varied from (0.72±0.80) GPa to (1.26±0.62) GPa under small external forces, implying the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Similar findings were observed for Aβ oligomers using all atom MD simulations, namely, extending the Aβ (9-42) protofilament length was found to introduce an overtwist in the protofibril structure which in turn resulted in a high deviation from the starting conformation and eventually a breakage of the β-sheets. Prior MD analyses on the deformation of Aβ (1-40) amyloid fibrils have also revealed that fibril breakage under mechanical loading ( i.e. , compressive and tensile strain) was preceded by torsional twisting deformation. ,, Besides, results from AFM and nanoindentation analysis have indicated that twisted β-sheets of hαS and glucagon are weaker or have lower elasticity modulus at the twist sections. Based on the simulation findings, any vulnerable point within the cross-β structure consistently reduces the ability of fibrils to withstand physical stress. , …”
Section: Results and Discussionsupporting
confidence: 58%
“…Similar findings were observed for Aβ oligomers using all atom MD simulations, namely, extending the Aβ (9-42) protofilament length was found to introduce an overtwist in the protofibril structure which in turn resulted in a high deviation from the starting conformation and eventually a breakage of the β-sheets. Prior MD analyses on the deformation of Aβ (1-40) amyloid fibrils have also revealed that fibril breakage under mechanical loading ( i.e. , compressive and tensile strain) was preceded by torsional twisting deformation. ,, Besides, results from AFM and nanoindentation analysis have indicated that twisted β-sheets of hαS and glucagon are weaker or have lower elasticity modulus at the twist sections. Based on the simulation findings, any vulnerable point within the cross-β structure consistently reduces the ability of fibrils to withstand physical stress. , …”
Section: Results and Discussionsupporting
confidence: 58%
“…This large range in moduli is common for amyloid fibrils and indicative of their structural heterogeneity. For example, AFM‐based nanoindentation studies estimated that the elastic moduli of glucagon amyloid fibrils range from 0.72 ± 0.80 GPa to 1.26 ± 0.62 GPa under small compressive forces while the moduli of insulin amyloid fibrils ranged from 5 to 50 MPa …”
Section: Measuring Mechanical Properties Of Single Molecules and Filamentioning
confidence: 99%
“…Therefore, studying their shell mechanical properties, especially the mechanical property of single NP-P- 17 and force−volume mapping can be used to measure the elastic modulus of protein molecules and fibers. 18,19 By combining AFM with reflection interference contrast microscopy, the elastic modulus of polymer capsules can be measured. 20 We measured the mechanical properties of hollow silica spheres by combining AFM and reflection interference contrast microscopy.…”
Section: Introductionmentioning
confidence: 99%